High-performance infrared photodetection beyond bandgap limitation based on surface plasmon resonance in sub-stoichiometry molybdenum oxide nanostructures. (1st April 2023) - Yu, Yuanfang; Zhong, Fan; Li, Ruizhi; Cui, Yueying; Wu, Jianfeng; Zhang, Jialin
Abstract: High-performance photodetectors in the near-infrared (NIR) regime are essential for many advanced applications, such as optical communication, intelligent driving, and imaging system. However, conventional photoconductive infrared detectors commonly suffer from slow response speed and narrow spectral response. Here, we demonstrate a high performance NIR photodetector based on plasmonic sub-stoichiometry molybdenum oxide (MoO3−x ) nanostructures/graphene heterostructure. Empowered by surface plasmon resonance induced near-field enhancement in MoO3− x and the subsequent hot-electron injection (HEI), a fast response time (rise time ∼6.7 μ s, decay time ∼12.5 μ s), high responsivity (3.3 A/W), low noise equivalent power (∼4.9 pW/Hz 1/2 ), as well as wide response range from visible light to NIR is obtained at room temperature. The weak carrier–phonon interaction in graphene prevents the relaxation of injected hot electrons and enables efficient electron extraction. The response speed is nearly four orders of magnitude improved compared with other graphene-based hybrid devices with similar device structures. Moreover, the interfacial HEI breaks the bandgap limits of molybdenum oxide and further extends the response spectrum of the device to conventional band (C-band) of optical communication. Our proposed device architecture offers new strategy for developing high-performance infrared photodetectors.